Autumn fertilization of Quercus ilex ssp. ballota (Desf.) Samp. nursery seedlings: effects on morpho-physiology and field performance - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER (Annals of Forest Science, 2011)
& Background The Holm oak (Quercus ilex ssp. ballota [Desf.] Samp.) is an evergreen tree widely distributed in the western Mediterranean Basin. Forest restoration programs using this species have enjoyed only limited success, and knowledge concerning the effect of fertilization on plant quality and post-transplantation response is sparse. & Methods We assessed the effect of autumn fertilization using different doses of nitrogen, phosphorus, and potassium (70.0 mg N, 30.5 mg P and 58.1 mg K during the growing phase for all plants; and 30.0 vs 1.5 mg N, 13.1 vs 0.3 mg P and 24.9 vs 0.5 mg K during the hardening phase, depending on the fertilization treatment) on the seedling characteristics and field performance of Holm oak. & Results and Conclusions Autumn fertilization, especially with N, did not decrease plant quality but improved overall growth, root growth capacity, cold hardiness, and the nutritional content of nursery-grown seedlings. However, autumn fertilization had only a small effect on field performance, which was affected only by K fertilization, probably because of the adequate N and P nutrient status of all the plants and the mild weather conditions of the field plot. In our site, which had a mild winter climate, late autumn out-planting was more successful than was midwinter out-planting.
Keywords: Cold hardiness; Field performance; Holm oak; Nursery fertilization; Nutritional status

Two provenances of Quercus ilex ssp. ballota (Desf) Samp. nursery seedlings have different response to frost tolerance and autumn fertilization - Andivia, Enrique; FERNÁNDEZ, MANUEL; VÁZQUEZ-PIQUÉ, JAVIER; Alejano, Reyes (European Journal of Forest Research, 2011)
Despite evidences that Holm oak has a high plasticity and great adaptability, there is limited or contradictory knowledge of the morphological and physiological variability of this species. Holm oak has been widely used for reforestation projects in Mediterranean areas, but has frequently shown poor ﬁeld performance. We hypothesized that Holm oak has inter-population differences in physiological responses to abiotic stressors that could affect reforestation success. The inﬂuence of nursery culture on the characteristics of Holm oaks from different provenances has not been explored in depth. Thus, we studied the effect of nursery autumn fertilization on morphological traits, frost tolerance, root growth potential, and nutritional status of two Spanish provenances of Holm oak, La Alcarria (a region with inland Mediterranean climate) and Sierra Morena Occidental (a region with a warm coastal Mediterranean climate). There were signiﬁcant differences between the provenances in frost tolerance, biomass allocation, and leaf nutrient content, suggesting a role of genetic factors. The leaves of seedlings from La Alcarria had less visual damage at -12C than seedlings from the warmer provenance (45% vs. 92%). Seedlings from La Alcarria, compared to those from Sierra Morena, had higher leaf P concentration (0.17% vs. 0.15%), greater stem diameter (3.1 mm vs. 2.7 mm), lower shoot-to-root dry mass ratio (0.46 vs. 0.53), and lower slenderness (4.03 vs. 5.31). For both provenances, N autumn fertilization improved growth, root growth potential, cold hardiness, and nutritional status of seedlings. We suggest that forest reforestation programs should consider to a greater extent Holm oak provenances and their tolerances to different abiotic stressors.
Keywords: á autumn fertilization; á reforestation á; Adaptation; adaptation á cold hardiness; Autumn fertilization; Cold hardiness; Holm oak; holm oak á provenance; provenance; Reforestation